Tuning the Properties of Protein-Based Polymers Using High-Performance Orthogonal Translation Systems for the Incorporation of Aromatic Non-Canonical Amino Acids - Gueta, Osher; Sheinenzon, Ortal; Azulay, Rotem; Shalit, Hadas; Strugach, Daniela S.; Hadar, Dagan; Gelkop, Sigal; Milo, Anat; Amiram, Miriam (Frontiers in Bioengineering and Biotechnology, 2022)
The incorporation of non-canonical amino acids (ncAAs) using engineered aminoacyl-tRNA synthetases (aaRSs) has emerged as a powerful methodology to expand the chemical repertoire of proteins. However, the low efficiencies of typical aaRS variants limit the incorporation of ncAAs to only one or a few sites within a protein chain, hindering the design of protein-based polymers (PBPs) in which multi-site ncAA incorporation can be used to impart new properties and functions. Here, we determined the substrate specificities of 11 recently developed high-performance aaRS variants and identified those that enable an efficient multi-site incorporation of 15 different aromatic ncAAs. We used these aaRS variants to produce libraries of two temperature-responsive PBPs—elastin- and resilin-like polypeptides (ELPs and RLPs, respectively)—that bear multiple instances of each ncAA. We show that incorporating such aromatic ncAAs into the protein structure of ELPs and RLPs can affect their temperature responsiveness, secondary structure, and self-assembly propensity, yielding new and diverse families of ELPs and RLPs, each from a single DNA template. Finally, using a molecular model, we demonstrate that the temperature-responsive behavior of RLPs is strongly affected by both the hydrophobicity and the size of the unnatural aromatic side-chain. The ability to efficiently incorporate multiple instances of diverse ncAAs alongside the 20 natural amino acids can help to elucidate the effect of ncAA incorporation on these and many other PBPs, with the aim of designing additional precise and chemically diverse polymers with new or improved properties.